Thickness and gamma-ray effect on physical properties of CdO thin films grown by pulsed laser deposition - Nasir, Eman M. (Iraqi Journal of Physics, 2019)
Polycrystalline Cadmium Oxide (CdO) thin films were prepared using pulsed laser deposition onto glass substrates at room temperature with different thicknesses of (300, 350 and 400)nm, these films were irradiated with cesium-137(Cs-137) radiation. The thickness and irradiation effects on structural and optical properties were studied. It is observed by XRD results that films are polycrystalline before and after irradiation, with cubic structure and show preferential growth along (111) and (200) directions. The crystallite sizes increases with increasing of thickness, and decreases with gamma radiation, which are found to be within the range (23.84-4.52) nm and (41.44-4.974)nm before and after irradiation for thickness 350nm and 400nm respectively, The dislocation density, microstrain and number of crystallites per unit surface area, decreases with increasing of thickness, while they increases with gamma radiation. From the atomic force microscope (AFM), the grain size of CdO films decrease from 96.69nm before radiation to 89.49 nm after gamma radiation and RMS roughness increases for the irradiated sample from 4.26nm to 4.8nm, increase in the surface roughness is advantages as it increases the efficiency of the CdO solar cells. The optical properties for thin CdOfilms with different thickness before and after gamma irradiation have been determined and reveals direct energy gap. It is decrease with the increase of thickness, while it is increase after gamma irradiation. These films a promising candidate for the window layer in solar cells and other possible optoelectronic application.